2010
DOI: 10.1183/09031936.00034410
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment of obstructive apnoea and stroke outcome: a randomised controlled trial

Abstract: The aim of the present study was to assess the impact of nasal continuous positive airway pressure (nCPAP) in ischaemic stroke patients followed for 2 yrs.Stroke patients with an apnoea-hypopnoea index o20 events?h -1 were randomised to early nCPAP (n571; 3-6 days after stroke onset) or conventional treatment (n569). The Barthel Index, Canadian Scale, Rankin Scale and Short Form-36 were measured at baseline, and at 1, 3, 12 and 24 months. The percentage of patients with neurological improvement 1 month after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
157
2
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(170 citation statements)
references
References 53 publications
(63 reference statements)
1
157
2
10
Order By: Relevance
“…They found no significant impact of CPAP treatment on all-cause mortality after two years of follow-up (HR, 0.62; 95% CI, 0.11-3.46). 29 The two other intervention studies are cohort studies with follow-up between five and seven years. 28,24 The study by Martínez-García et al concludes that patients with an AHI ≥ 20 and adequate CPAP compliance had hazard ratios that were not different from patients with an AHI < 20 in terms of both fatal and nonfatal cardiovascular events.…”
Section: How Cpap Affects Stroke and Tia Outcome In Patients With Sdbmentioning
confidence: 99%
See 1 more Smart Citation
“…They found no significant impact of CPAP treatment on all-cause mortality after two years of follow-up (HR, 0.62; 95% CI, 0.11-3.46). 29 The two other intervention studies are cohort studies with follow-up between five and seven years. 28,24 The study by Martínez-García et al concludes that patients with an AHI ≥ 20 and adequate CPAP compliance had hazard ratios that were not different from patients with an AHI < 20 in terms of both fatal and nonfatal cardiovascular events.…”
Section: How Cpap Affects Stroke and Tia Outcome In Patients With Sdbmentioning
confidence: 99%
“…24,28,29 The definition of SDB varied from an AHI of 10 events/hour in combination with excessive daytime sleepiness to 20 events/hour. Compliance rates varied from 11% 28 to 72%, 29 with a mean of 37%. Parra et al contributed with the only randomized controlled trial identified on this topic.…”
Section: How Cpap Affects Stroke and Tia Outcome In Patients With Sdbmentioning
confidence: 99%
“…Several randomized controlled studies have evaluated the use of CPAP among patients with acute ischemic stroke or TIA, but they have been limited by short follow‐up or small sample size 1, 3, 4, 5. The largest of the randomized trials observed (N=126) patients with acute stroke with sleep apnea over a 2‐year period 6. Patients were randomly assigned to receive either fixed‐pressure CPAP or usual care.…”
Section: Introductionmentioning
confidence: 99%
“…However, randomized controlled trials were not strong enough to show this effect. Some studies found that CPAP improved 1 or more neurologic function outcomes, sleepiness, or mood, [13][14][15]47 whereas the others found no benefit of CPAP treatment in these areas. [113][114][115] However, the negative studies had small sample sizes and patients had low CPAP compliance, which may have affected the results.…”
Section: Early Treatment Of Obstructive Sleep Apnea In Stroke Rehabilmentioning
confidence: 99%
“…11 There is growing evidence that treatment of coexisting OSA with continuous positive airway pressure (CPAP) or mandibular advancement devices can successfully treat OSA, resulting in improved rehabilitation outcomes and improved health-related quality of life. [12][13][14][15] …”
Section: Introductionmentioning
confidence: 99%